IMPLEMENTATION OF THE MERDEKA CURRICULUM POLICY AT MADRASAH ALIYAH AL WASHLIYAH, TEBING TINGGI CITY - Fadila Rahayu Utami; Audia Junita; Beby Masitho Batubara (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the implementation of the Merdeka Curriculum policy at Madrasah Aliyah Al Washliyah, Tebing Tinggi City, as part of the national education policy. The Merdeka Curriculum is designed to provide flexibility for educational units and educators in carrying out learning oriented toward strengthening essential competencies and students’ character. This research employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation involving informants consisting of the head of the madrasah, vice principal for curriculum affairs, teachers, students, parents, madrasah supervisors, and the madrasah committee. The analysis of policy implementation in this study uses the theoretical framework of Van Meter and Van Horn, which includes policy standards and objectives, resources, communication among implementers, characteristics of implementing organizations, social, economic, and political environments, as well as the attitudes of policy implementers. The results indicate that the implementation of the Merdeka Curriculum policy at Madrasah Aliyah Al Washliyah, Tebing Tinggi City, has been running fairly well; however, it still faces several obstacles, particularly in terms of human resource readiness, availability of facilities and infrastructure, and optimization of coordination among policy implementers. Therefore, strengthening educator capacity, supporting learning facilities, and adaptive madrasah management are needed so that the implementation of the Merdeka Curriculum policy can be carried out more optimally.